Layer 2/3 Pyramidal Neurons of the Mouse Granular Retrosplenial Cortex and Their Innervation by Cortico-Cortical Axons - Robles, Rita M.; Domínguez-Sala, Eduardo; Martínez, Salvador; Geijo-Barrientos, Emilio (Frontiers in Neural Circuits, 2020)
The retrosplenial cortex forms part of the cingulate cortex and is involved in memory and navigation. Its ventral region, the granular retrosplenial cortex, or GRSC, is characterized by the presence, of small pyramidal neurons with a distinctive late-spiking (LS) firing pattern in layer 2/3. Using in vitro brain slices of the mouse GRSC we have studied the electrophysiological properties and synaptic responses of these LS neurons, comparing them with neighboring non-LS pyramidal neurons. LS and non-LS neurons showed different responses during cortical propagation of epileptiform discharges. All non-LS neurons generated large supra-threshold excitatory responses that generated bursts of action potentials. Contrastingly, the LS neurons showed small, and invariably subthreshold excitatory synaptic potentials. Although both types of pyramidal neurons were readily intermingled in the GRSC, we observed differences in their innervation by cortico-cortical axons. The application of glutamate to activate cortical neurons evoked synaptic responses in LS neurons only when applied at less than 250 µm, while in non-LS neurons we found synaptic responses when glutamate was applied at larger distances. Analysis of the synaptic responses evoked by long range cortico-cortical axons (with origin at 1200 µm from the recorded neurons or in the contralateral hemisphere) confirmed that non-LS neurons were strongly innervated by these axons, while they evoked only small responses or no response at all in the LS neurons (contralateral stimulation, non-LS: 194.0±196.63 pA, n=22; LS: 51.91±35.26 pA, n=10; p=0.004). The excitatory/inhibitory balance was similar in both types of pyramidal neurons, but the latency of the EPSCs evoked by long range cortico-cortical axons was longer in LS neurons (contralateral stimulation non-LS: 8.13±1.23 ms, n=17; LS: 10.76±1.58 ms, n=7; p=0.004) suggesting a disynaptic mechanism. Our findings highlight the differential cortico-cortical axonal innervation of LS and non-LS pyramidal neurons, and that the two types of neurons are incorporated in different cortico-cortical neuronal circuits. This strongly suggests that the functional organization of the dorsal part of the GRSC is based on independent cortico-cortical circuits (among other elements).